(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Correction of anemia as a result of renal failure improves cardiovascular function and also provides significant cognitive and emotional benefits.The most appropriate route for iron supplementation has not been determined for patients with chronic renal failure who are not y et on dialysis. Objective:It is to compare the efficacy and tolerability of oral and intravenouse iron as an adjuvant therapy for erythropoieten treated anemic patients with chronic kidney disease in predialysis state. Methods:Forty five anemic patients with chronic kidney disease where prospectively randomized to receive an oral (ferrous sulfate 200 mg three time dialy ), or intravenous (300 mg iron dextran/ monthly) iron treatment, the duration of treatment was six months. Erythropoietin (rHuEpo) was simultaneously commenced and the dose adjusted according to pre-established protocol. Results:There were no significant differences in baseline patients characteristics between the two groups. four patients suffered possible allergic reaction to iron dextran. Hemoglobin response in the end of study was similar in two groups, but serum ferritin was significantly higher in the intravenous group.the Starting dose of rHuEpo temporarily discontinued in the patients on oral iron and the patients receiving iron dextran rHuEpo was increased after 3 months , final doses on EPO were (33.5) and (41.6) units /Kg/week respectively in the oral and intravenous group. Although gastrointestinal symptoms were more commonly reported in patients taking oral iron. Conclusions: In pre-dialysis patients; the efficacy of monthly 300 mg iron dextran administerd intravenously is not superior in regard to haemoglobin response and EPO dose as compared with daily oral dose of 300 mg of ferrous sulfate or equivalent. Key words: Chronic renal failure, Erythropoietin, Dialysis, Ferritin , Iron dextran